2012
DOI: 10.1007/s12035-012-8331-4
|View full text |Cite
|
Sign up to set email alerts
|

α-Synuclein Oligomers: an Amyloid Pore?

Abstract: In many human diseases, oligomeric species of amyloid proteins may play a pivotal role in cytotoxicity. Many lines of evidence indicate that permeabilization of cellular membranes by amyloid oligomers may be the key factor in disrupting cellular homeostasis. However, the exact mechanisms by which the membrane integrity is impaired remain elusive. One prevailing hypothesis, the so-called amyloid pore hypothesis, assumes that annular oligomeric species embed into lipid bilayers forming transbilayer protein chann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(74 citation statements)
references
References 63 publications
3
69
0
2
Order By: Relevance
“…This process dependent on the presence of negatively charged lipids being in a liquid disordered phase, while the headgroup is only of minor importance [35,36]. This behavior, which is comparable to monomeric α-synuclein suggests that mainly electrostatic interactions between the positively charged core of the oligomers and negatively charged lipid headgroups cause membrane binding [37,38]. In order to elucidate the mechanisms by which the α-synuclein oligomers permeabilize lipid bilayers, Subramaniam group tested different lipid mixtures in leakage experiments either based on the release of calcein from large unilamellar vesicles (LUVs) containing self-quenching concentrations of the probe or on measuring the influx of dithionite into LUVs labeled with 1-palmitoyl-2-6-[(7-nitro-2-1,3-benzoxadiazol-4-yl) amino] hexanoyl-phosphatidylcholine (C 6 -NBD-PC).…”
Section: A Gonzalez-horta Et Almentioning
confidence: 86%
“…This process dependent on the presence of negatively charged lipids being in a liquid disordered phase, while the headgroup is only of minor importance [35,36]. This behavior, which is comparable to monomeric α-synuclein suggests that mainly electrostatic interactions between the positively charged core of the oligomers and negatively charged lipid headgroups cause membrane binding [37,38]. In order to elucidate the mechanisms by which the α-synuclein oligomers permeabilize lipid bilayers, Subramaniam group tested different lipid mixtures in leakage experiments either based on the release of calcein from large unilamellar vesicles (LUVs) containing self-quenching concentrations of the probe or on measuring the influx of dithionite into LUVs labeled with 1-palmitoyl-2-6-[(7-nitro-2-1,3-benzoxadiazol-4-yl) amino] hexanoyl-phosphatidylcholine (C 6 -NBD-PC).…”
Section: A Gonzalez-horta Et Almentioning
confidence: 86%
“…Recently, it was demonstrated that the negative impact of aberrantly secreted ASN does not appear to involve internalization of this protein by the recipient neurons [40,41], but it depends on deregulation of various plasma membrane receptors most of which are Ca 2+ channels [28,42,43]. Alternatively, aberrant oligomeric structures of ASN were shown to evoke permeabilization of cellular membranes leading to uncontrolled Ca 2+ influx and synaptic vesicular depletion [27,[44][45][46][47]. In our studies, we generated an oligomeric species of ASN that are able to form annular pore-like structures and observed that treatment of PC12 cells with those oligomers leads to significant increase in cellular Ca 2+ concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, it became abundantly clear that, depending on the preparation protocol used, these oligomers exhibit a significant degree of structural and morphological heterogeneity, making it extremely challenging to identify a specific cytotoxic type of oligomer and to fully characterize these [12][13][14]. We, in particular, have extensively characterized the membrane binding and permeabilization capabilities of a specific, isolated, oligomeric species [15][16][17], and have focused on understanding the molecular composition and structural characteristics of this oligomeric species [10,18].…”
Section: Introductionmentioning
confidence: 99%